2020
DOI: 10.1126/scitranslmed.aaz2841
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-based treatment ameliorates NAFLD by modulating fatty acid oxidation, glutathione synthesis, and the gut microbiome

Abstract: Nonalcoholic fatty liver disease (NAFLD) including nonalcoholic steatohepatitis (NASH) has reached epidemic proportions with no pharmacological therapy approved. Lower circulating glycine is consistently reported in patients with NAFLD, but the causes for reduced glycine, its role as a causative factor, and its therapeutic potential remain unclear. We performed transcriptomics in livers from humans and mice with NAFLD and found suppression of glycine biosynthetic genes, primarily alanine-glyoxylate aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
153
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 77 publications
14
153
0
Order By: Relevance
“…This effect contributes to the hepato-protective properties of the polyphenol at the lowest dose. Moreover, a reduction in the abundance of Clostridum sensu stricto 1, whose link with NAFLD-related parameters has been reported elsewhere [51], was also observed in this group. This effect may well be driven by the antioxidant effect of pterostilbene, as reductions in Clostridum sensu stricto 1 abundance in response to antioxidant treatment (tempol) have been reported in a murine model of hepatic steatosis [52].…”
Section: Discussionsupporting
confidence: 86%
“…This effect contributes to the hepato-protective properties of the polyphenol at the lowest dose. Moreover, a reduction in the abundance of Clostridum sensu stricto 1, whose link with NAFLD-related parameters has been reported elsewhere [51], was also observed in this group. This effect may well be driven by the antioxidant effect of pterostilbene, as reductions in Clostridum sensu stricto 1 abundance in response to antioxidant treatment (tempol) have been reported in a murine model of hepatic steatosis [52].…”
Section: Discussionsupporting
confidence: 86%
“…On the HFD, glycine was elevated with XOS supplementation. Impaired glycine biosynthesis has been linked with hyperlipidemia and steatohepatitis and, conversely, administration of glycine in a tripeptide form to mice alleviated both conditions [63]. Notably, the levels of hypoxanthine were decreased by XOS independent of dietary fat.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that glycine may be directly related to the occurrence of NAFLD. Glycine significantly alleviates NAFLD in experimental mice by regulating fat oxidation, blood metabolite levels, gut microbiota composition, and glutathione synthesis (Rom et al, 2020). Furthermore, fibroblast growth factor-15/19 is a bile acid-induced gut hormone in the late fed phase that acts to decrease hepatic lipogenesis.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%